História e ficção em Manaus do século XX: "Dois Irmãos" de Milton Hatoum - Luiz, Lucas da Silva (2020)
This work aims to analyze the fictional work as an instrument and source for the historian's research, extracting elements from the narrative that makes it possible to understand its social, political and economic scenario, in addition to its importance as a modality of artistic languages. For this purpose, our main object and source is the work Dois Irmãos (2000) by Milton Hatoum, whose narrative takes place during the years 1920 to 1960, in Manaus, featuring a series of historical events in the city, which help to understand the construction of Manaus in turn of the 19th to the 20th century. In addition, we will also understand in the work, the importance of the author Milton Hatoum, for the national scene, highlighting his personal and academic trajectory, and thinking about how his productions influence the current critical thinking. Therefore, we try to think about the importance of Dois Irmãos in the construction of the city of Manaus from the triad: author, work and public. In addition, we aim to highlight how the Milton Hatoum represents its political and economic scenario through his fictional work.